CHILDHOOD IDIOPATHIC STEROID RESISTANT NEPHROTIC SYNDROME, DIFFERENT DRUGS AND OUTCOME - Shah, Syed Sajid Hussain; Hafeez, Farkhanda (Journal of Ayub Medical College Abbottabad, 2015)
Background: The management of steroid resistant nephrotic syndrome (SRNS) is quite difficult in paediatric patients. Not only the remission is difficult but also these patients are at risk of progression to end stage renal disease (ESRD). The goal of treatment is either to achieve complete remission or even partial remission as it is the most important predictor of disease outcome. Methods: This study was conducted at The Children's Hospital, Lahore from February 2014 to May 2015. The SRNS patients of either sex between ages of 1-12 years were included with histology showing mesangioproliferative glomerulonephritis (MesangioPGN), focal segmental glomerulosclerosis (FSGS) or minimal change disease (MCD). Patients were given different immunosuppressant drugs and steroid 30 mg/m2 alternate day therapy on case to case basis and kept on regular follow up to check for response and adverse effects. Results: Total of 105 patients included, 63 (60%) male and 42 (40%) female patients. The age ranges from 1.08 to 12 years, mean age of 6.53 years and SD of ±3.17. Tacrolimus was the most common drug used 43 (41%) patients followed by cyclosporine in 38 (36.2%) patients, while Mycophenolate mofetil (MMF) was prescribed in 21 (20%) patients. Complete response was in 96 (91.4%) initially while partial response was seen in 8 (7.6%) patients. On follow up, 92 (87.6%) patients showed complete response and partial response was in 5 (4.7%) patients. Cushingoid features and hypertrichosis were the most common adverse effect seen. Conclusion: Steroid resistant nephrotic syndrome can be managed well with various immunosuppressant drugs and steroids but treatment should be individualized according to clinical presentation, disease histology and cost/social factors. Keywords: Steroid Resistant Nephrotic Syndrome, cyclosporine, tacrolimus, immunosuppressant, outcome